Pemikiran Sa’īd Ramadhān Al-Būthī Terhadap Isu-isu Feminisme (Kajian atas Penafsiran Sa’īd Ramadhān Al-Būthī terhadap Ayat-ayat Hijab, Kepemimpinan Perempuan, Hak Waris, dan Poligami) - ; Firdausiyah, Umi Wasilatul (Islamic Religious Education Departement, 2022)
This study aimed to elaborate the thoughts of Muhammad Sa'īd Ramadhān al-Būthī regarding women and Islamic teachings that are considered discriminatory against women. As for several Islamic teachings discussed in this study, specifically hijab, women's leadership, inheritance rights, and polygamy. This research is library research and uses a qualitative approach. The theory used in this research is Hans George Gadamer's theory of effective hermeneutics. The results of this study are: 1) Hijab does not isolate women from all activities in life. But an extreme understanding of QS. an-Nur: 31 that caused disturbance to women which led to the decline of Islam; 2) Women's leadership is justified as long as they are not the head of state with certain conditions; 3) QS. an-Nisa: 11 (li adz-dzakar mitsl haẓẓi al-untsayayn) is not a general rule in the distribution of inheritance. This rule only applies in certain conditions; 4) Polygamy is questioned by Western feminists because of the fundamental differences in perceptions between Islam and the West in seeing the essence and concept of marriage and adultery; 5) True equality is equality that does not contradict the nature that God has given to humans.